Effect of time of day for harvest and postharvest treatments on the sugar metabolism of broccoli (Brassica oleracea var. italica) - Hasperué, Héctor Joaquín (2014)
Loss of sugars contributes to accelerate postharvest senescence of broccoli. Several treatments have been developed to delay senescence, but in many cases their effects on sugar metabolism were not analyzed. We studied the effect of harvest at different times of day (08:00, 13:00 and 18:00 h) and of several postharvest treatments as heat treatment (HT), modified atmosphere (MA) and 1-methylcylcopropene (1-MCP) on sugar levels and activities of enzymes related to sucrose and starch degradation. Harvesting at the end of day delayed the loss of chlorophylls and caused the lowest decrement in sugars, although no differences in invertase, sucrose synthase and β-amylase activities were detected among samples. Treatments of MA and 1-MCP caused a lower loss of glucose and fructose, while HT caused a lower decrement of sucrose. Treated samples maintained higher levels of chlorophylls. The treatments reduced the activity of invertase and sucrose synthase and induced higher levels of β-amylase activity. Harvesting at the end of day and performing simultaneously a MA treatment could be a good combination to maintain the green color of the inflorescence and sugar levels during postharvest of broccoli.